The Causes and Effects of Cosmetic Surgery on Kang Hanna as Seen in 200 Pounds Beauty (2006) - Jennifer Elisabeth Gunawan; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
200 Pounds Beauty (2006) is one of the popular Korean Romantic comedy films. It tells the story of Kang Hanna, a woman who faces societal discrimination due to her weight. This film explores her significant decision to undergo cosmetic surgery and the irony that her change does not make her completely happy. This study examines the causes and effects of Kang Hanna’s cosmetic surgery. The main theory for this study is the theory of body image. The findings show that Kang Hanna's negative body image and societal discrimination drive her decision to undergo cosmetic surgery. Additionally, it turns out that cosmetic surgery not only gives an initial effect on Kang Hanna but also further effects.